A Comparison of Caregiver Burden for Different Types of Dementia: An 18-Month Retrospective Cohort Study - Huang, Wen-Chien; Chang, Ming-Che; Wang, Wen-Fu; Jhang, Kai-Ming (Frontiers in Psychology, 2022)
Background This study aimed to elucidate the influence of dementia etiologies on the degree of caregiver burden and determine which factors predict a high caregiving burden. Methods This 18-month retrospective cohort study enrolled 630 patients and their caregivers from the Dementia Center of Changhua Christian Hospital. The care team performed face-to-face interviews every 6 months, for 18 months from when a diagnosis of dementia was made. The primary outcome was the change in Zarit Burden Interview (ZBI) scores. Generalized estimating equations were used for the longitudinal data analysis. Results Participants with Lewy body disease (LBD) had a significantly higher caregiving burden compared with those with Alzheimer's disease (AD) (β = 3.83 ± 1.47, Wald = 6.79, p = 0.009) after adjusting for patient and caregiver features. Caregivers of mixed-type dementia and frontotemporal dementia (FTD) experienced a greater burden than caregivers of AD, at 6- and 18-month follow-up. Patients with more severe dementia, neuropsychiatric symptoms, being cared for by more than two caregivers, or utilizing social resources were associated with higher ZBI scores; the depressive mood of caregiver also predicted higher ZBI scores. Conclusion This longitudinal study demonstrated that caregiver burden was influenced by the underlying dementia etiology of patients. The dementia care team should provide personalized education and transfer patients and caregivers to appropriate resources, especially for high-risk populations.